2021
DOI: 10.3390/children8050421
|View full text |Cite
|
Sign up to set email alerts
|

Successful Postnatal Cardiopulmonary Resuscitation Due to Defibrillation

Abstract: An asphyxiated term neonate required postnatal resuscitation. After six minutes of cardio-pulmonary resuscitation (CPR) and two doses of epinephrine, spontaneous circulation returned, but was shortly followed by ventricular fibrillation. CPR and administration of magnesium, calcium gluconate, and sodium bicarbonate did not improve the neonate’s condition. A counter shock of five Joule was delivered and the cardiac rhythm immediately converted to sinus rhythm. The neonate was transferred to the neonatal intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Thirty-four articles (87.2%) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] stated the patients’ gestational ages. The described neonates ranged from 25 +2 to 40 +4 weeks of gestation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-four articles (87.2%) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ] stated the patients’ gestational ages. The described neonates ranged from 25 +2 to 40 +4 weeks of gestation.…”
Section: Resultsmentioning
confidence: 99%
“…In 22 articles (56.4%) [ 7 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ] including 39 neonates (34.5%), rhythm disturbances were diagnosed immediately or within the first hours after birth. In 6 articles (15.4%) [ 8 , 34 , 35 , 36 , 37 , 38 ] the 62 described neonates (54.9%) were classified into an age group between birth and four weeks post-partum.…”
Section: Resultsmentioning
confidence: 99%
“…The case presentation by Mileder et al [ 11 ] is the first reported case of a newborn with perinatal asphyxia, who required postnatal resuscitation and defibrillation due to ventricular fibrillation following epinephrine administration. Based on this case, the authors suggest that health care providers managing neonatal resuscitation should be aware of the possible need for defibrillation, even though it may be very rare.…”
Section: Cardio-circulatory Supportmentioning
confidence: 99%
“…Besides its relevance for medication safety, there is also diagnostic relevance. In a recent case report in this journal, the postnatal management of a newborn with a congenital long QT syndrome was described [ 11 ]. The newborn had ventricular fibrillation at birth, and subsequently underwent therapeutic hypothermia [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent case report in this journal, the postnatal management of a newborn with a congenital long QT syndrome was described [ 11 ]. The newborn had ventricular fibrillation at birth, and subsequently underwent therapeutic hypothermia [ 11 ]. In such a scenario, one needs to compare QTc intervals collected during therapeutic hypothermia to relevant reference values.…”
Section: Introductionmentioning
confidence: 99%